Respuesta :
Answer:
QR = 3
Step-by-step explanation:
given Q is the midpoint of PR , then
PQ = QR , that is
3x = x + 2 ( subtract x from both sides )
2x = 2 ( divide both sides by 2 )
x = 1
Then
QR = x + 2 = 1 + 2 = 3
Answer:
QR = 3
Step-by-step explanation:
since Q is the midpoint, then PQ is the same as QR. so we equate the two as follows:
3x = x+2
then find x as shown below.
3x-x = 2 ( I grouped the like terms)
2x = 2. now divide by 2 to find x
x= 1,
since QR is x+2, now substitute x for 1
1+2 =QR
3 is the answer.
.thanks